Characterizing the curing behavior and high-temperature performance of epoxy-resin modified asphalts. (24th October 2022) - Zhang, Zhu; Liang, Jiale; Hu, Jiaqi; Li, Jiusu; Ni, Fujian
Highlights: The relationship between the content offunctional group was determined by infrared spectrum. The linear viscoelastic region of epoxy asphalt with different content was determined. The influence of epoxy resin on the performance of epoxy asphalt was studied. Abstract: This study was undertaken to quantify and analyze the microscopic morphology and curing reaction of epoxy asphalt (EA) modified with 2%, 5%, 10%, 20%, 30%, and 40% epoxy resin (ER) contents. The functional group changes and the ER dispersion before and after the curing reaction, at the micro level, were comparatively evaluated using the infrared spectroscopy and fluorescence microscopy. The influence of various ER contents on the high-temperature performance of EA was also analyzed and quantified, at macro level, using the dynamic shear rheometer (DSR). The research results showed that the particle size of the ER molecules after curing is more significant than before the curing reaction. When the ER content is low, the EA turned into a continuous phase. The peak area of the distinct functional groups in the EA was found to be linearly correlated with the quantitative content of the ER. The strain sweep results showed that the linear viscoelastic region of the EA shrinks after curing. The higher the ER content, the smaller the strain in the linear viscoelastic region. The frequency scanning results showed that the ER significantly increased the composite shear modulus ( G* ). The rutting factor ( G*/Sin δ ) showed that when the ER content exceeds 20%, the high-temperature deformation resistance of EA increases and vice versa. The test results of multiple stress creep recovery (MSCR) showed that the deformation recovery ability is significantly improved with increased ER contents after curing. As analyzed using the coefficient of variation (COV), the high-temperature DSR rheological indicated satisfactory statistical reliability with COV values less than 30%.